Local Politics and Local Planning: A Case Study of Hamilton, Ontario, 1915-1930 - Terpstra, Nicholas (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1985)
A study of the goals and strategies of planning in Hamilton shows that concentration of professional reports and civic planning boards alone is too limited to assess the local fate of the city planning movement and its constituent emphases of beautification and efficiency. The municipal advisory Town Planning Board (TPB) appointed in 1915 and the report commissioned from engineer-planner Noulan Cauchon in 1917 reflected the co-existence of the two emphases among Hamilton planning advocates. Post-war changes in the composition of the TPB and the development of ad hoc political alternatives to zoning reduced the TPB's political influence and led by 1923 to its abandonment by prominent beautifiers. While the ineffectual advisory TPB continued until completion of its zoning plan in 1928, the beautifiers moved to administrative parks and roads boards whose provincially legislated powers and budgets made them more effective vehicles for the realization of long-standing plans which had been re-iterated in Cauchon's report and pursued unsuccessfully through the TPB. By 1930, the efficiency planners had disappeared while the beaufifiers had overcome political challenges to their plans for scenic boulevards and a major expansion of the park system.